Improving Student Satisfaction in Islamic Higher Education: The Role of Academic Services and Lecturer Performance (Quantitative Study of PTKI in Riau) - Zalisman, Zalisman (LP. Ma'arif Janggan Magetan, 2025)
This study aims to analyze the influence of academic services and lecturer performance on student satisfaction at Islamic higher education institutions. Using a quantitative approach, data was collected through the distribution of questionnaires to students and analyzed using multiple linear regression and Pearson correlation. The results of the analysis indicate that both independent variables have a positive and significant contribution to student satisfaction levels, with faculty performance (β = 0.487) having a greater influence than academic services (β = 0.352). These findings emphasize the importance of faculty members in enhancing the quality of students' learning experiences, both in academic and developmental aspects. Based on these results, it is recommended that Islamic higher education institutions strengthen their academic service systems and prioritize faculty professional development focused on effective teaching, student engagement, and ethical leadership.